Pelatihan Parenting Model Hurier Untuk Meningkatkan Komunikasi Interpersonal Orang Tua Siswa Sdn 03 Pagi Pulau Panggang - Happy Karlina Marjo; Wirda Hanim; Rike Ulandari (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
Education plays a strategic role in shaping knowledgeable, cultured, and sustainable individuals and nations. Efforts to enhance learning motivation among elementary school students require the active involvement of multiple stakeholders, particularly effective communication between homeroom teachers and parents, as well as interpersonal communication between parents and their children. High-quality family interpersonal communication contributes to the development of healthy relationships, positive self-concept, empathy, and self-confidence in children, which in turn supports learning motivation. This community service program aimed to improve parents’ interpersonal communication skills through a parenting training program based on the HURIER model developed by Brownell (1996), which encompasses listening skills of Hearing, Understanding, Remembering, Interpreting, Evaluating, and Responding. The training was implemented for parents of students at SDN 03 Pagi Pulau Panggang using a combination of Focus Group Discussions (FGD), material delivery, and practical assignments. A total of 28 parents participated in the program. Program evaluation was conducted through pre- and post-tests to measure improvements in parents’ interpersonal communication skills, as well as partner satisfaction assessments regarding the implementation of the training. The results showed that after the training, 21.43% (6 parents) were categorized as having high interpersonal communication skills, 53.57% (15 parents) were in the moderate category, and 25% (7 parents) remained in the low category based on the HURIER model. Overall, the HURIER-based parenting training program was considered effective in strengthening parents’ roles in supporting elementary school students’ learning motivation. The output of this community service activity is a scientific article published in a national journal.